Pengaruh Pendidikan Kristen melalui Kelompok Tumbuh Bersama terhadap Pertumbuhan Rohani - Noni Yutersi; Andreas Fernando; Analita Analita (MANTHANO: Jurnal Pendidikan Kristen, 2022)
Abstract: God's will for His people is to grow into conformity with the image of His son. But in the reality of life not all people can continue to grow as ideally. The challenges of life and the demands of economic needs in particular in the era of the Covid-19 pandemic are obstacles in realizing spiritual growth. Through Christian Education in the group growing together is not just taught, but guided and strengthened, edifying each other so that it has an impact on spiritual growth together. The purpose of this study is to test and prove the influence of Christian Education through growing together groups on spiritual growth. This study used a correlational method. The results showed that the implementation of Christian education through groups to grow together had an impact on increasing the spiritual growth of the people. Through the learning process in Christian Education the group grows together which mutually expands life experiences, shares experiences in the application of God's word, reminds, strengthens each other and learns to implement the values of the Christian faith taught, becoming a joint encouragement that has an impact on spiritual growth.Abstrak: Kehendak Allah bagi umatNya adalah bertumbuh menjadi serupa dengan gambar anakNya. Namun dalam realita kehidupan tidak semua umat bisa terus bertumbuh sebagaimana idealnya. Tantangan kehidupan dan tuntutan kebutuhan ekonomi secara khusus di era pandemic covid-19 menjadi hambatan dalam mewujudkan pertumbuhan rohani. Melalui Pendidikan Kristen dalam kelompok tumbuh bersama tidak hanya sekedar diajar, melainkan dibimbing dan saling menguatkan, meneguhkan, sehingga berdampak pada pertumbuhan rohanis ecara bersama-sama. Tujuan penelitian ini untuk menguji dan membuktikan pengaruh Pendidikan Kristen melalui kelompok tumbuh bersama terhadap pertumbuhan rohani. Penelitian ini menggunakan metode korelasional. Hasil penelitian menunjukkan bahwa pelaksaan Pendidikan Kristen melalui kelompok tumbuh bersama berdampak pada peningkatan pertumbuh rohani umat. Melalui proses pembelajaran dalam Pendidikan Kristen kelompok tumbuh bersama yang saling membagi pengalaman hidup, membagi pengalaman dalam penerapan firman Tuhan, mengingatkan, saling menguatkan dan saling belajar mengimplementasikan nilai-nilai iman Kristen yang diajarkan, menjadi dorongan bersama-sama yang berdampak pada pertumbuhan rohani.